#### 2.872   ODE No. 872

$y'(x)=\frac {-6 x^3 y(x)+\frac {12 x^6}{5}+14 x^{7/2}-6 x^3-5 \sqrt {x} y(x)+10 x-5 \sqrt {x}-5}{x \left (2 x^3-5 y(x)+10 \sqrt {x}-5\right )}$ Mathematica : cpu = 0.0446531 (sec), leaf count = 215

$\left \{\left \{y(x)\to \frac {1}{5} \left (2 x^3+10 \sqrt {x}-5\right )-\frac {\sqrt {-x \left (2 x^3+10 \sqrt {x}-5\right )^2-50 x \left (-\frac {2 x^6}{25}-\frac {4 x^{7/2}}{5}+\frac {2 x^3}{5}-2 x+2 \sqrt {x}+\log (x)\right )-25 c_1 x}}{5 \sqrt {-\frac {1}{x}} x}\right \},\left \{y(x)\to \frac {1}{5} \left (2 x^3+10 \sqrt {x}-5\right )+\frac {\sqrt {-x \left (2 x^3+10 \sqrt {x}-5\right )^2-50 x \left (-\frac {2 x^6}{25}-\frac {4 x^{7/2}}{5}+\frac {2 x^3}{5}-2 x+2 \sqrt {x}+\log (x)\right )-25 c_1 x}}{5 \sqrt {-\frac {1}{x}} x}\right \}\right \}$ Maple : cpu = 0.125 (sec), leaf count = 49

$\left \{ y \left ( x \right ) ={\frac {2\,{x}^{3}}{5}}+2\,\sqrt {x}-\sqrt {{\it \_C1}+2\,\ln \left ( x \right ) }-1,y \left ( x \right ) ={\frac {2\,{x}^{3}}{5}}+2\,\sqrt {x}+\sqrt {{\it \_C1}+2\,\ln \left ( x \right ) }-1 \right \}$